2010
DOI: 10.1007/s11947-010-0352-2
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling and Simulation of Maltodextrin Solutions Spray Drying to Control Stickiness

Abstract: Particle stickiness during spray drying can lead to operational problems or be used to perform agglomeration inside the chamber. A simplified computational fluid dynamics approach is proposed to simulate the spray drying of 40% w/w aqueous solutions of maltodextrin DE12 and DE21 in a pilot cocurrent spray dryer equipped with rotary atomizer. Drying was simulated at steady state considering the geometry of the equipment (drying chamber, air inlet, atomizer) and the close relation between drying air and product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The final moisture content and water activity (a w ) are also defined by the spray drying process (Huntington, 2004;Gianfrancesco et al, 2010) and are important parameters to maintain good quality of the powders obtained; Ananta et al (2005) suggest moisture values lower than 5% and a range of 0.15 to 0.3 of a w , to avoid agglomeration problems during transportation and storage. The moisture content and a w values of the powders obtained in this study, are within the suggested ranges.…”
Section: Quality Of L Casei Microencapsulated By Spray Dryingmentioning
confidence: 99%
See 1 more Smart Citation
“…The final moisture content and water activity (a w ) are also defined by the spray drying process (Huntington, 2004;Gianfrancesco et al, 2010) and are important parameters to maintain good quality of the powders obtained; Ananta et al (2005) suggest moisture values lower than 5% and a range of 0.15 to 0.3 of a w , to avoid agglomeration problems during transportation and storage. The moisture content and a w values of the powders obtained in this study, are within the suggested ranges.…”
Section: Quality Of L Casei Microencapsulated By Spray Dryingmentioning
confidence: 99%
“…Some fruits and vegetables rich in these kind of compounds are tubers, quince, celery, arthichoke, broccoli, carrots, banana, plum, oranges, and apples, among others (Chau & Huang, 2003;Altieri, Bevilacqua, & Sinigaglia, 2011). However, special attention must be given in choosing the mixture suspension to be used for microencapsulation by spray drying due to some stickiness problems in the drying chamber (Palzer, 2005;Gianfrancesco, Turchiuli, Flick, & Dumoulin, 2010) or during storage (Langrish & Chiou, 2008) which may affect the final product quality or spray drying efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows that droplets mainly stick to the walls in the upper main chamber, the lower main chamber and at the base of the bustle as in these regions the flow field streamlines are tightly curved and the particles traversing the streamlines impact with the walls. Gianfrancesco et al (2010) elaborated CFD model to simulate the spray drying of maltodextrin DE12 and DE21 in a pilot co-current spray dryer to control material sickness. They estimated zones and operating conditions for which particles could be sticky inside the chamber on the basis of the evolution of particle temperature, water content and glass transition temperatures.…”
Section: Wall Depositionmentioning
confidence: 99%
“…Due to their low glass transition temperature and hygroscopic nature, the dried products become sticky (Jaya and Das 2009). The stickiness of particles during the spray drying can lead to many operational problems as well as be responsible for the formation of agglomerations inside the chamber which may reduce product recovery (Gianfrancesco et al 2010).…”
Section: Introductionmentioning
confidence: 99%